MODERN PROGRAMS AND TECHNOLOGIES OF MUSIC EDUCATION - Umarova Aiman Iles qizi (American Journals, 2023)
Modern programs and technologies in the field of music are aimed at the learning process, which is a complex unity of the activities of the teacher and the activities of students, aimed at a common goal - equipping students with knowledge, skills, and their development and education. Any intellectual activity, in particular music, is provided by the functional work of the brain associated with the perception and processing of information. Teaching methods in the school system are mainly focused on the left hemisphere of the brain. The left hemisphere is responsible for speech and language abilities, reading and writing abilities. Helps to process information logically and consistently. The right hemisphere is responsible for the ability to music, dance and visual arts. But in the learning process, it is practically not involved.
Keywords: education, music, learning process, music activities, music teacher, modeling, imitation.